Analyzing gender, intersectionality, and multiple inequalities global, transnational and local contexts - Chow, Esther Ngan-ling, 1943-; Segal, Marcia Texler, 1940-; Tan, Lin. (Bingley, U.K. : Emerald, 2011)
The papers in this volume were selected and revised from among those presented at the conference: Gender and Social Transformation: Global, Transnational, and Local Realities and Perspectives, Beijing, China in 2009. Through case studies and interview data from across the globe we see how intersectionality and inequality are contextualized shaping womens agencies, gender relations, identity, the politics of belonging, power structures, institutional arrangements, and empowerment (self and/or collective) in local communities and cultures influenced by transnational and global networks and processes. Those who experience inequality, the politics of exclusion and social injustice by virtue of gender, ethnicity and/or class and other differences are the most vulnerable in the face of new adversities, including those that occur in response to globalization. Broader theoretical and methodological contexts for these nation- and region-specific studies are provided in essays by leading gender theorists. Divisions of labor, migration, war and peace-building are among the specific topics addressed in papers from China, India, Israel, Korea, Northern Ireland, Turkey, and the United States.
Analyzing gender, intersectionality, and inequality in global, transnational and local contexts / Marcia Texler Segal, Esther Ngan-ling Chow -- Globalization and multiple inequalities / Sylvia Walby -- Strategies of feminist research in a globalized world / Judith Lorber -- Masculinity research and global society / Raewyn Connell -- A theoretical view of the globalizing sex industry : world system position, local patriarchy, and state policy in South Korea / Kyoung-Ho Shin -- Globalization and locality : the gendered impact of the economic crisis on intersectionality, migration, and work in China / Esther Ngan-ling Chow, Yuchun Zou -- Gender, division of labor, and social mobility in small-scale restaurants in China / Tong Xin -- Gender and labor within the Turkish context of local development in the era of globalization / Dilek Hattatoglu -- Constructing gender across borders : a transnational approach / Peggy Levitt -- Transnational migration and transformation among African women in the United States : change-agents locally and globally / Mary Johnson Osirim -- An intersectional approach to the complexity of social support within German-Ukrainian transnational space / Anna Amelina -- Social security and aged widows in conflict situations : social transformation at the international border in northwest India / Abha Chauhan -- Diversity, activism, and global concerns in the U.S. peace movement / Laura Toussaint -- Women's absence in peace-building policies : the case of the feminist organizations in Israel / Rachel Amram.
Keywords: Sex discrimination -- Congresses